Documentation and Validation of Indigenous Plant-Based Remedies for Respiratory Ailments in the Chota Nagpur Plateau of Jharkhand: A Case Study - Sinha, Deepa; Kumar, Veermani; Patra, Kamal Kant; Mishra, Asha (American Journal of Biology and Natural Sciences, 2025)
An ethnobotanical survey was conducted among 50 informants from tribal communities of the Chota Nagpur Plateau to document and validate indigenous plant-based remedies for respiratory ailments. The demographic analysis revealed 30 males (60%) and 20 females (40%), with ages ranging from 35 to 85 years (mean 62 years), and 75% of informants over 60, highlighting the concentration of traditional knowledge among the elderly (Table 01). Traditional healers (vaidyas) constituted 60% of participants, followed by farmers (30%) and others (10%), emphasizing the role of experienced practitioners. A total of 45 medicinal plant species were recorded, of which eight species were primarily used for respiratory disorders (Table 02, Figure 01). Leaves were the most frequently used plant part, reflecting sustainable harvesting practices. Key species included Adhatoda vasica, Justicia adhatoda, Ocimum sanctum, Tinospora cordifolia, Zingiber officinale, Glycyrrhiza glabra, Solanum xanthocarpum, and Azadirachta indica, demonstrating both cultural significance and pharmacological potential. In vitro anti-urolithic assays, including calcium oxalate nucleation and aggregation tests (Tables 04–05, Figures 02–03), indicated dose-dependent inhibitory effects, with Glycyrrhiza glabra, Solanum xanthocarpum, and Ocimum sanctum showing the highest activity. The study provides scientific validation of traditional remedies, supporting their therapeutic use in respiratory health while emphasizing the need for documentation, conservation, and further pharmacological exploration to preserve tribal knowledge and promote sustainable utilization of medicinal plants in Jharkhand.